Retroperitoneal hematoma due to spontaneous lumbar artery rupture during fondaparinux treatment. Case report and review of the literature - Fortina, M.; Carta, S.; Del Vecchio, et al., E.O. (Acta Biomedica Atenei Parmensis, 2007)
We present the case of a 78 year-old man who developed a spontaneous rupture of the lumbar artery leading to a retroperitoneal hematoma while receiving fondaparinux therapy after a total hip replacement. A selective angiographic embolization stopped the bleeding. Fondaparinux was discontinuated and the patient presented a complete resolution of his medical status. Spontaneous hematomas has been well described during low molecular weight heparin (LMWH) treatment, expecially in elderly patients, but there are no previous reports of hematomas induced by fondaparinux.We reviewed the literature to identify the possible risk-factors of bleeding. Our review shows that even if many works suggest that fondaparinux is a safe and effective alternative to LMWH in the prevention of venous thromboembolism following major orthopaedic surgery, it should carefully be used in elderly people and patients with renal disfunction.